Oviposition Preference of the Cabbage Root Fly towards Some Chinese Cabbage Cultivars: A Search for Future Trap Crop Candidates - Fabrice Lamy; Laura Bellec; Amélie Rusu-Stievenard; Pauline Clin; Claire Ricono; Diane Olivier; Solène Mauger; Denis Poinsot; Vincent Faloya; Loïc Daniel; Anne Marie Cortesero (Insects, 2020)
The development of integrated pest management strategies becomes more and more pressing in view of potential harmful effects of synthetic pesticides on the environment and human health. A promising alternative strategy against Delia radicum is the use of trap crops. Chinese cabbage (Brassica rapa subsp. pekinensis and subsp. chinensis) is a highly sensitive Brassicaceae species previously identified as a good candidate to attract the cabbage root fly away from other crops. Here, we carried out multi-choice experiments both in the laboratory and in field conditions to measure the oviposition susceptibilities of different subspecies and cultivars of Chinese cabbages as compared to a broccoli reference. We found large differences among subspecies and cultivars of the Chinese cabbage, which received three to eleven times more eggs than the broccoli reference in field conditions. In laboratory conditions, the chinensis subspecies did not receive more eggs than the broccoli reference. We conclude that D. radicum largely prefers to lay eggs on the pekinensis subspecies of Chinese cabbage compared to the chinensis subspecies or broccoli. Some pekinensis cultivars, which received over ten times more eggs than broccoli in the field, appear especially promising candidates to further develop trap crop strategies against the cabbage root fly.